Unlocking Financial Potential: Self-efficacy Transforming Capability into Well-Being for Working Women - Priya Gupta,; Mamta Aggarwal,; Bamba, Meera (Organizations and Markets in Emerging Economies, 2025)
The primary purpose of this study is to identify the influence of financial capabilities on women’s financial well-being and to study the mediating influence of self-efficacy in this relationship in Delhi-National Capital Region (NCR). The data were collected through purposive sampling using a questionnaire distributed from February to May 2024 to Delhi-NCR women engaged in any economic activity. Delhi-NCR is a metropolitan area encompassing Delhi and its surrounding districts in neighbouring states. Data analysis was performed on 250 responses from working women using purposive sampling. Variance-based Partial Least Square Structure Equation Modelling (PLS-SEM) was applied to test the conceptual model. This study operationalizes and validates financial capabilities as a reflective higher-order construct formed by two dimensions such as financial literacy and inclusion. Findings illustrate that financial capabilities directly influence working women’s financial well-being, and this relationship was partially mediated by financial self-efficacy. To improve women workers’ financial well-being, such policies and programs should be tailored to boost women’s confidence levels and beliefs, education, and inclusion in the financial dimension. This study directs policymakers, government, employers, and financial institutions to build confidence levels among women by organizing workshops and programs, which promotes their financial well-being and ultimately empowers them financially.
Keywords: financial capabilities; Financial well-being; Financial self-efficacy; empowerment